Rare Case of Suicide by Run-Over Road Traffic Accident- Interpretation and Analysis of Medico-Legal Findings - Tsranchev1, Ivan; Timonov, Pavel; Fasova, Antoaneta; Mileva, Biliana; Goshev, Metodi; Ankov, Hristian; Stoeva, Velina; Ivanov, Biser (International Journal of Medical Toxicology and Forensic Medicine, 2026)
Background: In traumatic forensic cases, road accidents represent an essential percentage of morbidity and mortality. The majority of these are unintentional incidents that have the same manner of death. Case Presentation: A 42-year-old man, was admitted to the regional hospital in Pazardzhik with symptoms of epigastric pain, vomiting, and weight loss. Following a physical examination, additional ultrasound tests, laboratory tests, and gastroscopy, which included a biopsy, the results indicated a malignant tumor in the stomach with the morphological characteristics of middle-grade adenocarcinoma. On the fourth day of the diagnostic and treatment process, the patient voluntarily left the hospital without notifying the medical staff. Conclusion: Road traffic injuries are a significant cause of increasing mortality rates among young and middle-aged individuals globally. While suicide is less common among traffic-related fatalities, both accidents and suicides can contribute to road traffic deaths. Suicides continue to be a significant cause of mortality and morbidity worldwide. Understanding the issues surrounding these cases, especially the rarer forms of suicide, is crucial for preventing this negative social phenomenon.